Dynamic resource allocation with hidden volatility - Feng, Felix Zhiyu; Westerfield, Mark M. (Journal of Financial Economics, 2021)
We study a dynamic continuous-time principal-agent model with endogenous cash flow volatility. The principal supplies the agent with capital for investment, but the agent can misallocate capital for private benefit and has private control over both the volatility of the project and the size of the investment. The optimal incentive-compatible contract can yield either overly risky or overly prudent project selection; it can be implemented as a time-varying cost of capital in the form of a hurdle rate. Our model captures stylized facts about the use of hurdle rates in capital budgeting and helps to reconcile the mixed empirical evidence on the correlations among firm size, risk and managerial compensation.